Employment structure, casualization and wage differential in rural Uttar Pradesh: a disaggregated analysis - Mishra, Nripendra Kishore; Singh, Udai Bhan (Area development and policy, 2019)
A transformation of the rural employment structure of the Indian state of Uttar Pradesh has seen a movement of workers from agriculture to non-agricultural sectors, which was contingent upon regional and individual characteristics. The share of casual workers in non-farm employment grew steadily, especially in the construction sector. Almost 90% of casual labourers belonged to either the Schedule Castes/Scheduled Tribes or Other Backward Castes. This study confirms that the conversion of cultivators, especially small and medium farmers into casual labourers, implies distress-driven diversification. A multinomial logit regression shows that women and workers with lower educational levels and larger landholdings are less likely to be involved in non-farm activities.